2013
DOI: 10.5665/sleep.3244
|View full text |Cite
|
Sign up to set email alerts
|

A Gonadotropin-Releasing Hormone Agonist Model Demonstrates That Nocturnal Hot Flashes Interrupt Objective Sleep

Abstract: This menopause model demonstrates that nighttime vasomotor symptoms correlate with increased sleep fragmentation. These findings are consistent with a specific contribution of vasomotor symptoms to polysomnography-measured sleep interruption suggesting that nighttime vasomotor symptoms interrupt sleep in the setting of menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 40 publications
2
42
0
Order By: Relevance
“…Similar to men, 69% of healthy premenopausal women treated press.endocrine.org/journal/jcem with a GnRH agonist report VMS (19). It has been proposed that declining estrogen levels narrow the thermoneutral zone between core body temperatures that trigger sweating and shivering (20,21).…”
Section: Discussionmentioning
confidence: 97%
“…Similar to men, 69% of healthy premenopausal women treated press.endocrine.org/journal/jcem with a GnRH agonist report VMS (19). It has been proposed that declining estrogen levels narrow the thermoneutral zone between core body temperatures that trigger sweating and shivering (20,21).…”
Section: Discussionmentioning
confidence: 97%
“…A recent study that induced estrogen deficiency in healthy premenopausal women with a GnRH agonist directly demonstrated that hot flashes are associated with three factors: 1) an increase in episodes of waking after sleep-onset; 2) a decrease in perceived sleep efficiency; and 3) a statistically significant correlation between nocturnal VMS and sleep disruption (31). Although these data are informative, it has not been substantiated whether they apply in naturally postmenopausal women with continuously high gonadotropins.…”
Section: Association With Sleepmentioning
confidence: 95%
“…Using controlled experimental studies, we established that new-onset hot flashes disrupt sleep by increasing the amount of wake time after sleep onset (WASO) and the number of awakenings measured objectively with polysomnography (PSG) proportionate to the number of nighttime hot flashes reported in the morning upon awakening. 4 WASO and awakenings similarly increased in association with the number of nighttime hot flashes recorded during the night using skin conductance monitoring that does not rely on subjective perception of or recall for these symptoms. This observed effect of nighttime hot BRIEF SUMMARY Current Knowledge/Study Rationale: It is well known that self-reported hot flashes are associated with sleep complaints in menopause.…”
Section: Introductionmentioning
confidence: 94%
“…4,15 The device detects individual hot flash events in 60-s intervals by measuring transient changes in sternal skin conductance. The monitor was time-synched to the PSG.…”
Section: Vasomotor Symptomsmentioning
confidence: 99%
See 1 more Smart Citation